A Board Coaching Framework for Effective Nonprofit Governance: Staff Support, Board Knowledge, and Board Effectiveness. Issue 5 (19th October 2020) - Mason, Dyana P.; Kim, Mirae
ABSTRACT: Nonprofit boards of directors are responsible for the governance of their organizations. Despite a wide literature on board governance, empirical studies have focused primarily on board characteristics such as board size, frequency of board meetings, or board member characteristics. Building on prior literature, we use qualitative interview and survey data from nonprofit board members and executive directors, respectively, to develop a board coaching framework to better understand how board dynamics, in particular staff support for board activities, can influence overall board performance. Our findings suggest the need to recognize the central role executives and staff play in nonprofit governance.